Estudio Ergonómico y Antropométrico de la prótesis en sus Miembros Superiores - Chicaiza Herrera, Jorge Darío (2019)
In Ecuador there are people who have some physical disability they are: intellectual; physical; auditory visual; psychosocial, which are on conadis data base. The present work is oriented in on anthropometric and ergonomic study of people who have suffered some bad formation or dismemberment on manufacture superior members, in Ecuador there are few places where they are. Most prostheses are imported and then adapted to users, because there is no ergonomic and anthropometric study they are standardized and they aesthetic or functional. For example, the European vehicles are large because American individuals are large and Japanese, Chinese and Korean vehicles are small because they are short and you have to adapt to them so in Latin America there is no specific measure of height. Since there is no information from the Public Health Ministry of people with this disability, a universe of 19 people was found at Cotopaxi and Pichincha provinces in City of Latacunga and Quito. The research has a social, technical and economic impact where it will help in the subsequent designs of prostheses for upper limbs with the statistical data made on the growth of people at different ages and real measurements were obtained which is detailed in the back at this research